2016
DOI: 10.1093/europace/euv408
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rivaroxaban compared with vitamin K antagonists for peri-procedural anticoagulation in catheter ablation of atrial fibrillation: a systematic review and meta-analysis

Abstract: Rivaroxaban is increasingly used in patients undergoing catheter ablation of atrial fibrillation (AF). In the absence of large controlled trials, a comprehensive meta-analysis of the literature appears to be the best way to obtain reliable evidence on rare peri-procedural outcomes such as thromboembolic or bleeding events. We aimed to provide a detailed analysis of currently available data on safety and efficacy of peri-procedural rivaroxaban in patients undergoing AF ablation. We performed a systematic search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
6
0
2
Order By: Relevance
“…Since we did not have access to individual patient data from all studies reviewed, the median of delta values for LVEF, EDV, NYHA and QRS was calculated and compared between the two patient groups by using the Mann-Whitney U test. Methodological quality of all studies was assessed using the methodological index for non-randomized studies (MINORS) [ 15 , 16 ]. Studies were defined to be low, moderate and high-quality studies based on their MINORS scores of < 8, < 16 and ≥ 16 points (Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since we did not have access to individual patient data from all studies reviewed, the median of delta values for LVEF, EDV, NYHA and QRS was calculated and compared between the two patient groups by using the Mann-Whitney U test. Methodological quality of all studies was assessed using the methodological index for non-randomized studies (MINORS) [ 15 , 16 ]. Studies were defined to be low, moderate and high-quality studies based on their MINORS scores of < 8, < 16 and ≥ 16 points (Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Metanálise que incluiu 7.400 pts de 15 estudos observacionais e 1 randomizado reportou tendência a menor taxa de eventos TE nos pacientes que receberam rivaroxabana em relação à varfarina (p = 0,052), com complicações hemorrágicas semelhantes (1,15% vs. 1,66%; p = 0,23). 19 Sawhney V et al compararam os DOAC (64% rivaroxabana) à varfarina, ininterruptos em 1.884 procedimentos de ablação de FA e não encontraram diferença entre os grupos em relação ao desfecho primário, composto por morte, TE ou sangramentos maiores (2,2% vs. 1,4%; p = 0,2). 20 Com esses resultados, agora mais consistentes, a ablação por cateter da FA sob uso ininterrupto de varfarina, dabigatrana ou rivaroxabana passou a ter recomendação classe I no último consenso de especialistas (HRS, EHRA, ECAS, APHRS, SOLAECE), publicado em 2017.…”
Section: Discussionunclassified
“…18 A meta-analysis that included 7400 pts from 15 observational and 1 randomized studies reported a trend toward lower rate of TE events in patients receiving rivaroxaban compared to warfarin (p = 0.052), with similar bleeding complications (1.15% vs. 1.66%; p = 0.23). 19 Sawhney V et al compared DOAC (64% rivaroxaban) to warfarin, uninterrupted in 1884 AF ablation procedures, and found no difference between the groups in relation to the primary outcome consisting of death, TE or major bleedings (2.2% vs. 1.4% p = 0.2). 20 With these now more consistent results, catheter ablation of AF under uninterrupted use of warfarin, dabigatran or rivaroxaban is now class I recommendation in the latest expert consensus (HRS, EHRA, ECAS, APHRS, SOLAECE), published in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In previous meta‐analyses, Zhao et al suggested that NOACs were associated with decreased incidence of bleeding complications when compared to uninterrupted or interrupted VKAs, whereas Vamos et al and Vallakati et al identified that there were no differences between NOACs and VKAs in terms of any bleeding complications. It should be noted that there is heterogeneity in the VKA regimens used in the different observational studies.…”
Section: Discussionmentioning
confidence: 99%